Встановлення та юридичне оформлення кордонів Української РСР з сусідами – встановлення та часткові уточнення кордонів з РСФРР в 1920-х рр. - Макарчук, Володимир; Makarchuk, Volodymyr (Видавництво Львівської політехніки, 2024)
Пропонована увазі читача стаття є першою частиною циклу з 5 статей, присвяченого встановленню кордонів Української СРР (та її правового продовження за союзною Конституцією 5 грудня 1936 р. Української РСР) з сусідніми радянськими республіками – РРФСР, Білоруською СРР (БРСР) та Молдавською АСРР (з 1936 р. – Молдавською АРСР) та правонаступницею останньої – Молдавською РСР. Вказано, що кордони УСРР з РСФРР (тогочасні назви республік) у 1920-х рр. встановлювалися не на основі етнографічного принципу, а з міркувань економічної доцільності при пріоритетному врахуванні інтересів Москви. Наприклад, до складу РРФСР відійшло місто Суджа, яке свого часу проголошувалося більшовиками як одна зі столиць “радянської України”. Російська сторона усіляко акцентувала увагу на тому, що ті чи інші спірні регіони важливі для забезпечення РСФРР хлібом, вугіллям та робочою силою, не зупиняючись перед односторонніми діями без погодження з українською стороною та до актів саботажу під час передання тих чи інших спірних територій до складу УСРР. Позиції українців ослаблювало “інтернаціональне” керівництво республіки, заведене компартійною дисципліною. Водночас теперішній кордон між незалежними Україною та рф не має підлягати перегляду, Україна не претендує на будь-які російські території, зокрема Курщину, про що у серпні 2024 р. була зроблена спеціальна заява українського МЗС.

This article is the first part of a series of 5 articles dedicated to the establishment of the borders of the Ukrainian SSR (and its legal continuation under the Union Constitution of 5 December 1936 of the the Moldavian ASSR (Moldavian Autonomous Socialist Soviet Republic; since 1936 – the Moldavian Autonomous Soviet Socialist Republic) and the latter’s legal successor – the Moldavian SSR. The author points out that the borders of the Ukrainian SSR and the RSFSR (the then names of the republics) in the 1920s were established not on the basis of the ethnographic principle, but for reasons of economic expediency, with priority consideration of Moscow’s interests. For example, the city of Sudzha, which at one time was proclaimed by the Bolsheviks as one of the capitals of “Soviet Ukraine”, became part of the RSFSR. The Russian side emphasised in every possible way that certain disputed regions were important for providing the RSFSR with bread, coal and labour, not stopping short of unilateral actions without the consent of the Ukrainian side and acts of sabotage during the transfer of certain disputed territories to the Ukrainian SSR. The position of the Ukrainians was weakened by the “international” leadership of the republic, driven by the Communist Party’s discipline. At the same time, the existing border between independent Ukraine and the Russian Federation should not be revised, and Ukraine does not claim any Russian territories, including Kursk, as stated in a special statement by the Ukrainian Foreign Ministry in August 2024. Ukrainian SSR) with the neighbouring Soviet republics – the RSFSR, the Belorussian SSR (BSSR) and
Demarcation and legalisation of the borders of the Ukrainian SSR with its neighbours – establishment and partial clarification of boundaries with the RSFSR in the 1920s.
Keywords: кордони УРСР; сучасні кордони України; правове регулювання національного питання у внутрішній політиці Союзу РСР; borders of the Ukrainian SSR; modern borders of Ukraine; legal regulation of the national question in the internal policy of the USSR; 340